Strategi Pemasaran dan Diferensiasi Produk dalam Menghadapi Persaingan Impor: Studi Kasus PT. Soka Cipta Niaga - Firsta Agdies Eka Nugroho; Rika Rismayanti; Ganjar Santika (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The rapid growth of the Muslim population, both in Indonesia and globally, has driven an increasing need for products to support worship, including Muslim socks. PT Soka Cipta Niaga (PT SCN), a producer of Muslim socks under the brand